Umbrales de lluvia para el desencadenamiento de inestabilidades de ladera en el norte de Portugal y de España: estado del arte - Valenzuela, Pablo (2023)
A great number of works focused on the calculation of empirical rainfall thresholds for the triggering of landslides have been develo-ped in the northern areas of Portugal and Spain. Because of a review, 103 thresholds have been compiled. More than 30% of them have not yet been published. The comparison of four regional thresholds highlights relevant differences linked to the use of multiple methodo-logies to define the critical rainfall conditions.